Enhanced quality of service control scheme with high availability for self-optimising wireless sensor network. (1st January 2014) - Wang, Hao-Li; Tsai, Rong-Guei; Huang, Ray Yueh-Min
Whereas various aspects in wireless sensor networks (WSNs) have been extensively investigated, the quality of service (QoS) control remains relatively unexplored. QoS is defined as the number of awakened sensors in a WSN. Sensor deaths (caused by running out of battery) and sensor replenishments (caused by redeployment of new sensors) contribute to the difficulty in controlling QoS in WSNs. A previous study developed a QoS control scheme based on the Gur Game paradigm. The Gur Game-based scheme can effectively adjust active sensors to a desired QoS without the information of total sensor numbers. However, this approach is only applicable to a range of desired QoS. This limitation decreases the availability and the application of the Gur Game-based scheme. The present study proposes an enhanced QoS control scheme, namely, the high-availability QoS control (HAQC), which increases the availability range by applying a divide-and-conquer concept. The present study also uses the distribution used in the previous study. Simulations that compared our technique with those applied in other studies in various environments demonstrate that our scheme ensures a robust and high-availability sensor network capable of dynamically adjusting active sensors.